Prodigy [compact disc, unabridged] : a Legend novel - Lu, Marie, 1984- (Lu, Marie, 1984- Legend novel., 2013)
June and Day arrive in Vegas just as the unthinkable happens: the Elector Primo dies, and his son Anden takes his place. With the Republic edging closer to chaos, the two join a group of Patriot rebels eager to help Day rescue his brother and offer passage to the Colonies. They have only one request: June and Day must assassinate the new Elector. It's their chance to change the nation, to give voice to a people silenced for too long.